Parasitic swine fauna and control planning program - ΓΕΩΡΓΟΥΛΑΚΗΣ ΓΙΑΝΝΗΣ EMM. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study attempt to discuss some of the recent findings contributing to a better understanding of parasitism in Greek swine. The incidence and prevalence of endoparasites was shown in four age groups (sows in farrowing houses, 6-8 weeks old pigs, 35-40 kg pigs, market weight pigs) was carried out on 450 animals from 14 farms. The animals found infected by Ascaris, Trichuris, Oesophagostomum, Strongyloides, Coccidia and Balantidium. The carried out study showed the multiparasitism which prevails in Greek intensive pork production and recommend a continuing deworming program in order to control parasitism that is a must in modern swine production and management.